Reduced-rank estimation of genetic parameters for egg production traits and cluster analyses with predicted breeding values - Freitas, Luara Afonso de [UNESP]; Savegnago, Rodrigo Pelicioni [UNESP]; Grupioni, Natalia Vinhal [UNESP]; Ramos, Salvador Boccaletti; Stafuzza, Nedenia Bonvino [UNESP]; Pereira de Figueiredo, Elsio Antonio; Schmidt, Gilberto Silber; Ledur, Monica Correa; Munari, Danisio Prado [UNESP] (Taylor & Francis As, 2018)
The aims of this study were to compare the suitability of the multi-trait (MUT) model to estimate genetic parameters with that of 13 reduced-rank principal component models (PC1 to PC13), and then to explore the additive genetic patterns of the breeding values obtained from these using clustering analyses of egg production traits. A total of 1,212 records were used to estimate genetic parameters using the MUT and PC models. The PC4 model was the best representation of the data since it had a lower AIC value and was more parsimonious than the MUT model. The estimated heritability of the age at the first egg (AFE) trait from this model was 0.28 +/- 0.06, and the estimated genetic correlation between AFE and total egg production (TP) was -0.52 +/- 0.23. Potentially animals from cluster 2 are more likely to be in the selected group to help improve the egg production.
Keywords: Genetic correlation; heritability; k-means; laying hens; Ward clustering